A sandwich technique for prevention of cerebrospinal fluid rhinorrhea and reconstruction of the sellar floor after microsurgical transsphenoidal pituitary surgery - Freyschlag, Christian F.; Goerke, Stephanie Alice; Obernauer, Jochen; Kerschbaumer, Johannes; Thomé, Claudius; Seiz-Rosenhagen, Marcel (Journal of neurological surgery. Part A, Central European neurosurgery, 2016)
Background: Cerebrospinal fluid (CSF) leaks are a well-known complication of transsphenoidal surgery. Several autologous and artificial grafts have been used to close the sellar floor in an attempt to prevent postoperative CSF rhinorrhea. Objective: To evaluate and describe a sandwich technique to close the sellar floor using autologous bone, absorbable gelatin sponge, and coated collagen fleece. Methods: We reviewed 50 consecutive patients between April 2010 and August 2011 who underwent transsphenoidal surgery ending with reconstruction of the sellar floor with a particular sandwich technique. Patients with an intraoperative CSF leak received an additional lumbar drain. Results: There were no cases of CSF rhinorrhea at postoperative follow-up after 6 weeks and no revision surgery. Conclusion: The proposed sandwich technique for closure of the sellar floor to the sphenoid sinus is a suitable alternative to autologous grafts and seems to be effective in preventing CSF rhinorrhea.
Gesehen am 06.05.2019
Published online June 19, 2015